2021
DOI: 10.1002/anie.202110900
|View full text |Cite
|
Sign up to set email alerts
|

CO‐Tolerant PEMFC Anodes Enabled by Synergistic Catalysis between Iridium Single‐Atom Sites and Nanoparticles

Abstract: Proton‐exchange membrane fuel cells (PEMFCs) are limited by their extreme sensitivity to trace‐level CO impurities, thus setting a strict requirement for H2 purity and excluding the possibility to directly use cheap crude hydrogen as fuel. Herein, we report a proof‐of‐concept study, in which a novel catalyst comprising both Ir particles and Ir single‐atom sites (IrNP@IrSA‐N‐C) addresses the CO poisoning issue. The Ir single‐atom sites are found not only to be good CO oxidizing sites, but also excel in scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…So far, although a variety of noble metal catalysts have been exploited, 12,16−18,21−24 few of them can work stably for the HOR current at a potential lower than 0.10 V under 100−1000 ppm of CO impurity in rotating disk electrode (RDE) tests. Moreover, in PEMFC tests, even 20 ppm of CO in H 2 will cause a significant degradation of Ptbased catalysts within 1 h. 6 Recently, Ru-based 25 and Irbased 26,27 HOR catalysts have been developed, exhibiting evidently enhanced CO tolerance compared with Pt-based catalysts. However, the HOR stability under a CO environment beyond 1 h is still a great challenge in this field, which impedes the application in PEMFCs.…”
Section: ■ Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…So far, although a variety of noble metal catalysts have been exploited, 12,16−18,21−24 few of them can work stably for the HOR current at a potential lower than 0.10 V under 100−1000 ppm of CO impurity in rotating disk electrode (RDE) tests. Moreover, in PEMFC tests, even 20 ppm of CO in H 2 will cause a significant degradation of Ptbased catalysts within 1 h. 6 Recently, Ru-based 25 and Irbased 26,27 HOR catalysts have been developed, exhibiting evidently enhanced CO tolerance compared with Pt-based catalysts. However, the HOR stability under a CO environment beyond 1 h is still a great challenge in this field, which impedes the application in PEMFCs.…”
Section: ■ Introductionmentioning
confidence: 63%
“…Moreover, in PEMFC tests, even 20 ppm of CO in H 2 will cause a significant degradation of Pt-based catalysts within 1 h . Recently, Ru-based and Ir-based , HOR catalysts have been developed, exhibiting evidently enhanced CO tolerance compared with Pt-based catalysts. However, the HOR stability under a CO environment beyond 1 h is still a great challenge in this field, which impedes the application in PEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, superior ORR performance of Co/CoN x -C with optimal 15 wt% Co composition should be mainly attributed to the good dispersion of Co species and the synergistic effect of CoN x sites and metallic Co clusters. [54][55][56][57] More importantly, the E 1/2 value of 15-Co/CoN x -C outperformed the commercial Pt/C (E 1/2 : 0.840 V vs. RHE) and the representative Co-based non-noble metal electrocatalysts towards ORR in alkaline media (Table S4 †). Notably, N-C shows a high HO 2…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the carbon supports doped with metallic single atoms, deliver a promoting effect on supported nanoparticles in several electrocatalytic reactions, which is lacked on the common carbon or N-doped carbon supports. For example, Yang et al [54] found that Ir NP @Ir SA -N-C catalysts with Ir single atoms and nanoparticles are highly active for hydrogen oxidation reaction in H 2 /CO mixture, while carbon-supported Ir and Pt nanoparticles are inactive due to the poisoning of CO. The Ru single atoms anchored by N-doped C and Ru or Ru alloyed nanoparticles also showed synergistic effects in promoting the HER activity.…”
Section: Fundamental Concepts In Electrocatalysismentioning
confidence: 99%